A comparative study of negative life events and depressive symptoms among healthy older adults and older adults with chronic disease. (December 2017) - Zhang, Han; Gao, Tingting; Gao, Jinglei; Kong, Yixi; Hu, Yueyang; Wang, Ruimei; Mei, Songli
Objective: This study aims to study internal relations and functionary mechanism between social support, coping style, negative life events and depressive symptoms and compare these relations in healthy older adults and older adults with chronic disease. Design: A cross-sectional study was conducted in 2015. In total, 1, 264 older adults with chronic disease and 749 healthy older adults participated in this investigation which consist of socio-demographic characters, negative life events, social support, coping style and depressive symptoms. Results: The path and direction of variable function in healthy older adults were inconsistent with older adults with chronic disease. Older adults with chronic disease had more severe depressive symptoms and negative life events, and lower social support and positive coping style. Negative life events, subjective support, positive coping style and negative coping style were significantly predicted depressive symptoms. Objective support may weaken the influence of negative life events on depressive symptoms in chronic disease group. Utilization of support and positive coping style worsen the effect of negative life events on depressive symptoms in healthy older adults. Conclusion: This study implied that to improve their mental health, attention should be paid to the role of biological, psychological and social stress factors and its inherent law of interaction.